Psychometric Properties of the Oldenburg Burnout Inventory in a Portuguese Sample of Aircraft Maintenance Technicians - Reis, Cátia (2022)
Funding: PhD fellowship - PP - Coordenação de Aperfeiçoamento de Pessoal de Nível Superior, Grant/Award, Number: 88887150178/2017-00.